(untitled) (Per Musi, 2000)
The article is a study on a performance technique of the cello natural harmonics in which two adjacent nodes, of the same mode of vibration and on the samestring are touched simultaneously. The technique has three special utilities: first, it increases the number of nodes for the performance of some natural harmonics; second, it makes easier to perform musical passages in which harmonic tones are involved; third, it reinforces and assures the performance of any natural harmonic. Three examples of the application of the double-node technique to musical passages of the cello repertoire are presented.